(untitled) (Raparin Journal of Humanities (RJH), 2024)
This research is to build a scale for evaluating the natural geography book of high school under the light of general quality criteria. Knowing theextentof having a general quality measure in the geography book of the11th grade of literary readings in the eyes of teachers and expert supervisors, according to the gender change (male and female) General quality in the booklet to achieve these goals, the researcher used the method of description and analysis as an example of the research which was made in (70) teachers and supervisors of geography in male and female gender All three educations in the east and west of Sulaimaniyah and Chamchamal education for the school year (2021-2022), which were selected in a symbolic way, research tools Which consisted of a survey form consisting of 86 sections, which was divided into (7) items, and this was the benefit of the previous research. The researcher after preparing the tool and directing it The truth and stability of using Person’s partner in the rate of (0.815) then the researcher also performed it on the example of the research, after analyzing and presenting the survey to Using Person’s co-ordination, appropriate center, Test (T.test) after being certain of the truth, the researcher used the(spss) statistical program. Finally, the researcher reached the goals that each (7) sections of the 11th grade natural geography book which are (objective, they were (aim, art, activity, motivation, teaching, language, subject, content) and they were not accepted.